Mechanical properties and performances of contemporary drug-eluting stent: focus on the metallic backbone. (4th March 2019) - Chichareon, Ply; Katagiri, Yuki; Asano, Taku; Takahashi, Kuniaki; Kogame, Norihiro; Modolo, Rodrigo; Tenekecioglu, Erhan; Chang, Chun-Chin; Tomaniak, Mariusz; Kukreja, Neville; Wykrzykowska, Joanna J.; Piek, Jan J.; et al.
ABSTRACT: Introduction : Drug-eluting stents (DES) are still the standard of care in percutaneous coronary intervention (PCI) since the fall of bioresorbable scaffolds with respect to safety. The unbeatable advantage of a metallic stent when compared with a scaffold is a stronger mechanical property and more sustainable vascular support. Recent development of contemporary metallic stent has focused on the reduction of strut thickness. However, there will always be a trade-off between improvement in deliverability, flexibility, and radial strength. Areas covered : This review aims to discuss the designs of metallic stent platform and mechanical properties as well as mechanical performance of contemporary DES from bench studies and clinical trials. Expert opinion : Mechanical properties of stents affect short- and long-term clinical outcomes. Ultrathin-strut DES have become popular and clinical trials have shown impressive results. Thinner struts may improve device flexibility and deliverability but the radial strength and longitudinal integrity might have been compromised as well. Ultrathin-strut cobalt chromium or platinum chromium DES will become standard of care in PCI practice in the near future. Information on the stent design, stent material and mechanical properties of the stent are essential for a rational selection of the appropriate stent in selected lesions and patients.